1984
DOI: 10.1002/app.1984.070290305
|View full text |Cite
|
Sign up to set email alerts
|

Thermal degradation of polyester thermosets prepared using dibromoneopentyl glycol

Abstract: SynopsisPolyester thermosets have been prepared from maleic anhydride, phthalic anhydride, dibromoneopentyl glycol, and styrene, and their thermal degradation has been studied. Thermogravimetry has shown that degradation in air occurs in three main stages. For the 10% bromine polyester, the weight losses corresponded to 16.376, 69.7%, and 13.9% of the original polymer weight-the temperatures of the DTG peak maxima being 217OC, 345OC, and 530°C, respectively. Infrared analysis of the residues showed that above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The representatives of the weight derivatives over temperature, seen in Figure 5 b, clearly show two principal decomposition steps during TGA under air (oxidative) environment. A similar behavior is reported in the literature [ 34 , 35 , 36 ]. These two peaks occur in two consecutive stages between the 290 °C and 550 °C temperature range, with the former at the onset of the neat polyester thermal degradation, and the latter at the end of the polyester thermal degradation.…”
Section: Resultssupporting
confidence: 89%
“…The representatives of the weight derivatives over temperature, seen in Figure 5 b, clearly show two principal decomposition steps during TGA under air (oxidative) environment. A similar behavior is reported in the literature [ 34 , 35 , 36 ]. These two peaks occur in two consecutive stages between the 290 °C and 550 °C temperature range, with the former at the onset of the neat polyester thermal degradation, and the latter at the end of the polyester thermal degradation.…”
Section: Resultssupporting
confidence: 89%
“…The temperature at which the maximum rate of weight loss was seen decreased as the proportion of brominated polyester resin increased, as may be seen fromTable 6. The main zone of weight loss ended at an almost identical temperature for all three samples.Previous studies[17][18][19][20] have observed a similar slower initial stage of weight loss from pure phthalic acid-based polyester resins and attributed it to the release of phthalic anhydride, an initial degradation product of this type of polyester[17,19,21]. Skinner and co-workers[18] monitored the thermal degradation of a thermoset, brominated polyester resin in air using a TGA.…”
mentioning
confidence: 79%
“…Dibromoneopentyl glycol (DBNPG), as a brominated flame retardant, was developed in the 1970s. The products, such as flame‐retarded polyesters and phosphates, synthesized from DBNPG have been studied extensively. With a low bromine content, characteristic quaternary carbon atom, and dihydroxyl structure, DBNPG can act as the carbon source in IFRSs.…”
Section: Introductionmentioning
confidence: 99%